Expected Future Earnings, Taxation, and University Enrollment: A Microeconometric Model with Uncertainty - Frank M. Fossen; Daniela Glocker (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Taxation changes the expectations of prospective university students about their future level and uncertainty of after-tax income. To estimate the impact of taxes on university enrollment, we develop and estimate a structural microeconometric model, in which a high-school graduate decides to enter university studies if expected lifetime utility from this choice is greater than that anticipated from starting to work right away. We estimate the ex-ante future paths of the expectation and variance of net income for German high-school graduates, using only information available to those graduates at the time of the enrollment decision, accounting for multiple nonrandom selection and employing a microsimulation model to account for taxation. In addition to income uncertainty, the enrollment model takes into account university dropout and unemployment risks, as well as potential credit constraints. The estimation results are consistent with expectations. First, higher risk-adjusted returns to an academic education increase the probability of university enrollment. Second, high-school graduates are moderately risk averse, as indicated by the Arrow-Pratt coefficient of risk aversion estimated within the model. Thus, higher uncertainty among academics decreases enrollment rates. A simulation based on the estimated structural model indicates that a revenue-neutral, flat-rate tax reform with an unchanged basic tax allowance would increase enrollment rates for men in Germany because of the higher expected net income in the higher income range.
Keywords: H24; I20; I28; 330; University enrollment; income taxation; flat tax; income risk; risk aversion